A rare case of eosinophilic esophagitis and eosinophilic subserosal gastroenteritis with ascites - Šaban, Jovana; Milošević, Velimir (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Saban J, Milosevic V. A rare case of eosinophilic esophagitis and eosinophilic subserosal gastroenteritis with ascites. Turk J Gastroenterol 2019; 30(9): 851-3.